Exclusionary rule and evidentiary prohibition in American law - Stanković Bojana D. (Zbornik Radova: Pravni Fakultet u Novom Sadu)
The rules on the exclusion of evidence are one of the few rules, which, due to their characteristics, cannot be polarized into the Anglo-Saxon model and the European-continental model. A unique model of exclusion of evidence exists in American law, which is the creator of the exclusionary rule, while in other countries of the Anglo-Saxon system and the European-continental system, a relative system of exclusion is represented in its autonomous forms. Under the influence of numerous Anglo-American doctrines and judicial practice of courts in the USA, a system of absolute separation was established, which is based on the protection of the constitutional rights of citizens, with the fact that this approach was relativized over time through exceptions that were accepted in practice. In this paper, the author deals with the origin and characteristics of the exclusionary rule, the differences in relation to the relative system of extracting evidence and the most important evidentiary prohibitions, which arose as a con sequence of the violation of the constitutional amendments. The emergence of evidentiary prohibitions in the USA, especially those related to the prohibition of self-incrimination and the prohibition of Hearsay, is of great importance for these generally accepted institutes of Anglo-Saxon law, but also for the standards of the ECtHR, as shown by the practice of the highest judicial instance of the USA, which was analyzed in the paper.